HUBUNGAN ANTARA HARGA DIRI DAN PENYESUAIAN DIRI PADA PENYANDANG PASCA KECELAKAAN DI PANTI SOSIAL BINADAKSA BUDI PERKASA PALEMBANG - Arisandy, Desy (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2015)
This study aimed to investigate relationship between self esteem with adjustment self on disabel post accident at social home Binadaksa Budi Perkasa Palembang.Dependent variable in this study is adjustment self, while self esteem an independent variable. This research uses a scale of adjustment self and self esteem. This research uses quantitative methods. The sample used random sampling methode. The results of this research showed a significant relationship between self esteem with adjustment self on disabel post accident at social home Binadaksa Budi Perkasa Palembang with a value of r = 0.816, F = 127.155, p = 0.000 for the results ofsignificance (p) 0.000 mean value of p <0.01. So otherwise there is a very significant relationship. Peer group contributes to adjustment self  of 66.5%. Thus there are another 33.5% contributed by another factors that could trigger adjustment self on disabel post accident at social home Binadaksa Budi Perkasa Palembang.